2021
DOI: 10.1007/s11031-021-09879-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the learning environment in adolescents’ motivational development

Abstract: Past research has continuously shown that motivation in school declines across adolescence. To counteract potential declines in educational practice, the present study examines the motivational development of early and middle adolescent students within one school year and across two distinctive learning environments: a conventional teacher-directed learning environment and an individualized student-directed learning environment based on competency matrices. Based on a sample of 1153 (Mage = 13.97, SD = 1.37, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Limited research is available regarding the differences between self-directed and teacherdirected learning environments (Kulakow & Raufelder, 2020;Raufelder & Kulakow, 2021;Schweder & Raufelder, 2021b, 2021cSchweder et al, , 2020. The current trend in schools is to include self-directed learning modules (see Fig.…”
Section: The Present Investigationmentioning
confidence: 99%
“…Limited research is available regarding the differences between self-directed and teacherdirected learning environments (Kulakow & Raufelder, 2020;Raufelder & Kulakow, 2021;Schweder & Raufelder, 2021b, 2021cSchweder et al, , 2020. The current trend in schools is to include self-directed learning modules (see Fig.…”
Section: The Present Investigationmentioning
confidence: 99%
“…All students deserve a safe, respectful, positive, and caring learning environment in which they feel belonged, are respected and cared for, joyful, and responsible. Previous studies (e.g., Lizzio et al, 2002;Raufelder & Kulakow, 2021), which tend to focus on the school environment, have found connections between the ecological assets and students' academic achievement, self-efficacy, and satisfaction. Hamid et al (2013) suggested that students who perceive the ecological assets as more favorably tend to have greater learning achievement than those who do not.…”
Section: Motivations For Self-driven Learningmentioning
confidence: 92%
“…Martin (2021) reveals in his research that the technology's sophistication cannot be separated from the role of environmental support that can maximize it. The learning environment directly impacts academic activities (Haleva et al, 2021) and motivation of students (Raufelder & Kulakow, 2021). Thus, it can be said that the implementation of online learning applied at MAN 1 is inseparable from the learning environment and internal curriculum designs, which become the basis for supporting it.…”
Section: The Implementation Of Video-based Asynchronous Online Learni...mentioning
confidence: 99%